Engineered Ferritin Nanoparticles for the Bioluminescence Tracking of Nanodrug Delivery in Cancer. Issue 39 (28th August 2020) - Bellini, Michela; Riva, Benedetta; Tinelli, Veronica; Rizzuto, Maria Antonietta; Salvioni, Lucia; Colombo, Miriam; Mingozzi, Francesca; Visioli, Alberto; Marongiu, Laura; Frascotti, Gianni; Christodoulou, Michael S.; Passarella, Daniele; et al.
Abstract: The identification of a highly sensitive method to check the delivery of administered nanodrugs into the tumor cells is a crucial step of preclinical studies aimed to develop new nanoformulated cures, since it allows the real therapeutic potential of these devices to be forecast. In the present work, the ability of an H‐ferritin (HFn) nanocage, already investigated as a powerful tool for cancer therapy thanks to its ability to actively interact with the transferrin receptor 1, to act as an efficient probe for the monitoring of nanodrug delivery to tumors is demonstrated. The final formulation is a bioluminescent nanoparticle, where the luciferin probe is conjugated on nanoparticle surface by means of a disulfide containing linker (Luc‐linker@HFn) which is subjected to glutathione‐induced cyclization in tumor cell cytoplasm. The prolonged imaging of luciferase+ tumor models, demonstrated by an in vitro and an in vivo approach, associated with the prolonged release of luciferin into cancer cells by disulfide bridge reduction, clearly indicates the high efficiency of Luc‐linker@HFn for drug delivery to the tumor tissues. Abstract : A Luc‐linker@HFn nanoconstruct, where luciferin is conjugated on the surface of H‐ferritin nanoparticles by means of a self‐immolative linker, which is subjected to glutathione‐induced cyclization and release of luciferin in tumor cell cytoplasm is proposed. In vitro and in vivo bioluminescence monitoring into cancer cells demonstrates the efficiency of this nanoformulation for the transport of antitumor molecules to their target.